Formation of optical dark area (ODA) on high-cycle fatigue fracture surface of Al–Cu–Mg alloy at atmosphere induced by inner friction - Xinxiang Yu; Zhiguo Zhao; Dandan Shi; Xianli Shi; Yanli Jie; Wei Feng; Han Dai (Journal of Materials Research and Technology, 2021)
The formation of optical dark area (ODA) on high-cycle fatigue fracture surface of Al alloys at atmosphere is very common and questionable in the engineering fields. Herein, we discovered that the oxygen induced inner friction causes the serious Cu element segregation in the form of nanoparticles on the fatigue fracture surface at atmosphere, which forms the ODA in Al–Cu–Mg alloy. By increasing stress ratio or applying Vaseline coatings fatigue tests, the ODA can be absolutely eliminated simultaneously with a significant extension of their fatigue lives.